Correction: A desferrioxamine B squaramide ester for the incorporation of zirconium-89 into antibodies. Issue 77 (9th September 2016) - Rudd, Stacey E.; Roselt, Peter; Cullinane, Carleen; Hicks, Rodney J.; Donnelly, Paul S.
Abstract : Correction for 'A desferrioxamine B squaramide ester for the incorporation of zirconium-89 into antibodies' by Stacey E. Rudd et al., Chem. Commun., 2016, DOI: ; Web:10.1039/c6cc05961a .